Penentuan Jenis Kelamin Benih Ikan Betutu (Oxyeleotris marmorata Blkr.) dengan Teknik Truss Morphometrics - Atang Atang; Suhestri Suryaningsih; Muh. Nadjmi Abulias (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2015)
A study on The Gender Determination Of Betutu Germ (Oxyeleotris marmorata Blkr.) by Truss Morphometrics used survey method with Simple Random Sampling design, Betutu’s germ as sample were taken from Penjalin reservoir,  Brebes. The 26 distance of 13 pile points were based or Truss Morphometrics it were recorded as variables. The result of this research indicated that the size of Betutu’s A2 (origin anterior tip of snout at upper jaw – most posterior aspect of neurocranium), A4 (origin posterior point maxillary – origin of pelvic fin), B5 (origin of pelvic fin – origin of dorsal fin), B6 (origin of pelvic fin – origin of anal fin), D1 (insertion of anal fin – origin of lower caudal fin) and D3 (insertion of dorsal II fin – origin of lower caudal fin) can differentiate the gender of Betutu’s germ.